2012
DOI: 10.1016/j.jaccedu.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning: Does accounting education need it?

Abstract: a b s t r a c tProblem-based learning (PBL) has been used successfully in disciplines such as medicine, nursing, law and engineering. However a review of the literature shows that there has been little use of this approach to learning in accounting. This paper extends the research in accounting education by reporting the findings of a case study of the development and implementation of PBL at the Queensland University of Technology (QUT) in a new Accountancy Capstone unit that began in 2006. The fundamentals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 17 publications
4
67
0
26
Order By: Relevance
“…These results were in good agreement with the findings of Stanley and Marsden (2012) and suggest the use of problem-based learning (PBL) in accounting education. Additionally, the results in the present study confirmed that accounting educators could indirectly improve students' ACH through SRL strategies.…”
Section: Discussionsupporting
confidence: 86%
“…These results were in good agreement with the findings of Stanley and Marsden (2012) and suggest the use of problem-based learning (PBL) in accounting education. Additionally, the results in the present study confirmed that accounting educators could indirectly improve students' ACH through SRL strategies.…”
Section: Discussionsupporting
confidence: 86%
“…Um dos métodos aplicados foi o agrupamento dos alunos para reforçar que devem trabalhar em equipe para a resolução de problemas na Contabilidade. Esses métodos são não estruturados e podem ser comparados na prática (Stanley & Marsden, 2012). Soares (2008) destaca que o tema é novo para a área contábil, o que favorece novas pesquisas podendo utilizar diferentes disciplinas, ou todo o semestre de pesquisa para um maior número de estudantes na área de Contabilidade.…”
Section: Estudos Sobre Metodologias Ativasunclassified
“…Conclui-se que o objetivo do estudo foi atingido e que, no tópico explorado, os discentes absorveram conhecimento, melhoraram a comunicação e obtiveram confiança (Soares, 2008). Fazem-se necessárias novas pesquisas no campo da Ciência Contábil, pois a temática ainda é nova nessa área, com a utilização de mais dados, com número maior de disciplinas ou número maior de estudantes para a extensão da discussão (Stanley & Marsden, 2012;Soares, 2008).…”
Section: Estudos Sobre Metodologias Ativasunclassified
“…Breton (1999) demonstrated that the application of problem-based learning approach produced better results in terms of knowledge acquisition and aptitude to deal with problems in the long term. Using a case study detailing how problem-based learning was implemented in a final-year Accountancy Capstone unit in an Australian university, Stanley and Marsden (2012) also showed that students perceived problem-based learning to be effective, especially in terms of developing questioning, teamwork, and problem solving skills. Additionally, problem-based learning tasks can also be integrated into Accounting information system (AIS) curriculum to improve academic performance (Wilkin, 2014).…”
Section: Problem-based Learningmentioning
confidence: 98%